Das Vorabendprogramm im Schweizer Privatfernsehen und seine sprachliche Ferne zu Frauen - Honegger, Monique (My University, 2000)
Gender-adequate language in Swiss-German private TV. The personal references in Swiss-German private TV channels are obviously not gender-adequate. The masculin generic forms are currently used – in standard German as well as in Swiss-German dialect. As the texts and talks get more private or «intimate», more explicit female grammatical forms appear. It stricks that women themselves tend to use generic masculin forms when they designate themselves. The more formal character of the standard German language doesn’t seem to influence the gender-adequacy of reference. Channels and programs try to be as close to the everyday-life of their customers as possible. The everyday-life obviously doesn’t care about gender-adequate language. TV is not meant to show other realities than these.